Measuring and comparing functional business skills and knowledge among asnaf community in Malaysia - Yusoff, Mohd Nor Hakimin; Al Mamun, Abdullah; Ibrahim, Mohamed Dahlan; Hassan, Hasannuddin (2018)
This study aims (1) to determine the distribution of the components of functional business skills and knowledge among low-income households living across different geographical districts; (2) to assess the reliability of each dimension of entrepreneurial skills, and (3) to assess the validity and overall reliability of the entrepreneurial skills instrument. The study employed a cross-sectional approach. The sample of 800 low-income households in Kelantan, Malaysia, and the total of 200 respondents from each location were administered for the business skills and knowledge questionnaire for a period of one month, testing five dimensions of Financial Skills, Technical Skills, Communication Skills, Market Orientation, and Networking Skills. The study demonstrated that five dimensions were developed in the entrepreneurial skills construct. The validity of the formation of the five dimensions were proved through factor analysis. Based on the reliability and validity testing, this study ended with 34 items that fell into five dimension of Financial Skills, Technical Skills, Communication Skills, Market Orientation, and Networking Skills. Furthermore, it was found that the distribution of ‘financial skills’, ‘technical skills’ ‘communication skills’, ‘marketing skills’, and ‘networking skills’ are significantly different across the districts of Kelantan. Policy makers and other developmental organizations should therefore focus on interactive programs that could encourage participants towards increasing the level of knowledge and skills among the Asnaf particularly in the district of Jeli. Observing the positive business skills and knowledge which stimulates business success, this study recognizes the level of business knowledge among the Asnaf as moderately low.